Animals. - Schneider, Christiane; Gaita, Raimond (London : Haunch of Venison London, 2004)
Baumgarten, Lothar ; De Bruyckere, Berlinde ; Fritsch, Katharina ; Gallagher, Ellen ; Isaacs, John ; Kappos, Marina ; Kelley, Mike ; Macià, Oswaldo ; Mylayne, Jean-Luc ; Nauman, Bruce ; Onofre, João ; Potrc, Marjetica ; Sarcevic, Bojan ; Smith, Kiki ; Thater, Diana ; Trockel, Rosemarie ; Viola, Bill
Animals, Haunch of Venison, London, 22 June - 11 September 2004
Exhibition curated by Christiane Schneider
biog., ind. tent., gr. tent. p.54-70
boek